جماليات الأسلوب في الشعر الشعبي الجزائري ديوان "بسمات من الصحراء" لـ "حسان درنون" أنموذجا. - زقادة, شوقي (University of Eloued جامعة الوادي, 2023)
يمثل الشعر الشعبي مظهرا من مظاهر الثقافة الوطنية في الجزائر، و هو من أكثر الفنون الشعبية مقدرة على التعبير عن حاجات الفرد، وعلى ملامسة وجدان الجماعة، وتتمظهر من خلاله ملامح الهويّة المشتركة، وقد كان ولا يزال لسان العامّة وشاهد على التاريخ؛ ويمكن التأكد من أصالة هذا الشعر بعد تصفح دواوين شعرائه التي تميّز أصحابها على اختلاف الأغراض التي يعبّرون بها بالمحلية من جهة، وارتباطهم العميق بالتراث والتاريخ العربيين من جهة أخرى، ولا يخلو هذا الشعر من الجانب الفنّي والمتعة الجماليّة، ومن جمال التعبير ودقة التصوير، والشاعر حسان درنون ـ بلا شك ـ واحد من هؤلاء، وسنحاول في هذا المقال الكشف عن الملامح الأسلوبية والجمالية التي تميّزت بها قصائده في ديوان "بسمات الصحراء" من خلال تتبع البنيتين: التركيبية والدلالية. Folk poetry represents a manifestation of the national culture in Algeria, and it is one of the most popular arts capable of expressing the needs of the individual, touching the conscience of the group, and showing through it the features of the common identity, and it was and still is the tongue of the public and a witness to history ,The authenticity of this poetry can be confirmed after browsing the collections of his poets, whose authors were distinguished by the different purposes for which they express the locality on the one hand, and their deep connection to Arab heritage and history on the other, This poetry is not devoid of the artistic side, the aesthetic pleasure, the beauty of expression and the accuracy of embodiment, And the poet Hassan Darnoun is undoubtedly one of them, and in this article we will try to reveal the stylistic and aesthetic features that distinguished his poems in “Smells of the Desert” by tracing the two structures: synthetic and semantic.
مقال
Keywords: الأسلوب؛ حسان درنون؛ البنية التركيبية، البنية الدلالية. ; stylistics; Hassan Darnoun; structure synthetic; structure semantics.